Research Of Porous Concrete With Master Ease 5010 Mixed And Additional Rude Aggregate From Kedak Region - Hadi Mashuri; Ahmad Ridwan; Agata Iwan Candra; Faiz Muhammad Azhari; Ashabul Yamin (Litbang Pemas - Universitas Islam Lamongan, 2021)
Porous Concrete is a type of Concrete that has a cavity in its structure that allows liquid to flow through the cavity. This study aims to determine the effect of adding Master Ease 5010 admixture on the compressive strength and absorption capacity of porous Concrete. The method used in this research is an experimental method by making different tests in the laboratory. The sample used is 10 x 20 cm with a concrete age of 28 days. The tests carried out include compressive strength testing and absorption testing. The absorption test used the falling head method based on the ACI 522R. The results of the normal compressive strength test = 0.28 Mpa, the addition of Master Ease 5010 3% = 0.31 Mpa, and the addition of Master Ease 5010 5% = 0.416 Mpa while testing the absorption of Normal Porous Concrete = 1.406 mm/s, addition of Master Ease 5010 3% = 1,946 mm/s, addition of Master Ease 5010 5% = 2.196 mm/s. From these results, it can be seen that the addition of Master Ease 5010 is able to increase the compressive strength and absorption value of porous Concrete.